COMPETITIVENESS OF MOLDOVAN AGRI-FOOD EXPORTS AT THE REGIONAL LEVEL IN THE CONTEXT OF CURRENT CRISES - Vasilii SOVCOVICI; Viorica LOPOTENCO; Liliana STAVER (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the context of current crises, the competitiveness of Moldova's agri-food exports emerges as a primary topic of interest, given that they account for over 50% of the nation's total exports. This study investigates the competitiveness of Moldova's agri-food exports compared to three EU candidate countries - Georgia, Moldova, and Ukraine - and two EU member states - Poland and Romania. Using the Balassa Index, it analyzes the comparative advantages of these nations in the agri-food sector, with particular attention to the sub-categories of food products and vegetables. The results indicate a high competitiveness of Moldova in the exports of food products and vegetables, while the category of animal products shows comparative disadvantages. The study contributes to the literature by highlighting the dynamics of comparative advantages and recommends focusing on the development of the agri-food processing industry to improve the external trade structure. The research emphasizes the need for a strategic approach in adapting and integrating national agricultural and food systems into global value chains to maximize economic benefits in a changing regional and global landscape.